(3efGgL GdHMK GdYdej h efGgL JMbjb GdeNWhWGJ (B/s - (3TQjaj, YR GdOjfs ((3GdLRGFQ (B:s (3OGQ GdChWGf ,s, 2018)
(3jVe gPG GdcJGH Ydejf geG(B:(3GdHMK GdYdej h efGgL JMbjb GdeNWhWGJ GdbSe GdChd h gh efGgL GdHMK GdYdej abO YQV ajg HYV WQb GdHMK GdYdej hTQhWg h cjajI UfY GdghGeT h cjajI UfY GdagGQS hZjQ Pdc hNJeg GdcGJH HfeGPL eJfhYI dUfY ePcQI ePcQI GdJNQL (B, (3CeG GdbSe GdKGfj h gh efGgL JMbjb GdeNWhWGJ abO YQV ajg CSS h bhGYO JMbjb GdeNWhWGJ h cd GdeQGMd GdJj jeQ HgG GdHGMK dJMbjb Cj cJGH Ke RhO gPG GdbSe HfeGPL JhVjMjI (B. s
Keywords: (3GdHMK s; (3GdYdej s; (3GdeNWhWGJ s; (3efGgL s